Numerical Study on Discharging Characteristics of Entangled Cluster of Particles in Particle Bed - Huang, Xiaoli; Ge, Liang; Gui, Nan; Yang, X. T.; Tu, J. Y.; Jiang, S. Y. (Frontiers in Energy Research, 2021)
To better understand the flow features of particle cluster in particle bed, discharging of the particle entangled cluster were simulated by DEM. The particle entangled cluster was composed of eight particles connected by rigid bonds and the simulated entangled cluster models are divided into two types: axisymmetric u-particle and distorted z-particle. The simulation starts with the closed discharge outlet and the bonded clusters with different ID are randomly added from the entrance section. The particles fall freely and accumulate freely in the particle bed. The discharge hole opens after all the particles being stationary for a period. Then the particles are discharged from the particle bed under gravity. The discharging process is time-dependent bulk-movement behavior. There is not much mixing between layers on the boundary. The vertical end makes the packing loose, but also intensifies the interaction between particles due to entanglement. Consequently, the discharge features of particle entangled clusters of different included angles were quantified. The results show that the particle discharging speeds depend on entanglement angle (α of u-particle and η of z-particle) and discharging outlet diameter. A large included angle may play the role of retarding or inhibiting the discharging flowrate. Therefore, the entanglement of particles component also always plays the key role of retarding the discharge.